Design Of Robotic Leg Using Proportional Integral Deferential Controller with Computed Torque Control Method - Matteb, Zaineb Wared; Bakhy, Sadeq Hussein; Hadi, Nabil Hassan (Journal of Engineering and Sustainable Development, 2025)
Mobile robots are now crucial elements in manufacturing sectors. A five-link robot leg is fundamental for understanding robotic leg principles, modelled by a nonlinear differential equation. Numerical solutions are used when closed-form solutions become difficult for systems with higher degrees of freedom. This study focused on controlling the robot leg to reach the desired position by combining computed torque control with a PID (Proportional Integral Derivative) controller based on the motion equation derivation. The numerical solution implemented using MATLAB includes simulation and modelling, where Simulink tools are used for simulating dynamic systems and then evaluated against the computed torque control approach. Position errors for motor 1 and motor 4 were observed for 1 second and 10 seconds. Stability was achieved in the first motor after approximately 0.75 seconds. The second motor's movement stabilized after around 0.9 seconds, with the error value between input and output for 10 seconds starting at 0.06 and 6.1, stabilizing at zero within 1 second at motors 1 and 4, respectively. The system reached stability after approximately 0.3 seconds using computed torque with PID control, with gains (Kp, Kd, and Ki) set to (9500:10:20). Numerical simulation outcomes validate the controller's effectiveness in accurately tracking diverse trajectories.